TINJAUAN TEORITIS TENTANG MIGRASI PENDEKATAN RELASIONAL DATABASE KE PENDEKATAN OBJEK SISTEM INFORMASI AKUNTANSI - Weli , (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2005)
The object-oriented approach in system design and development is gaining popularity. Some literature in information system demonstrate that object-oriented approach is viewed as superior to conventional system development such as relational database approach. There were many advantages of object-oriented approach such as easier modeling, more efficient model reuse and more convenient maintenance. In this paper we introduce you to object-oriented design to Accounting Information Systems by migrate the relational approach to object-oriented approach based on entity relationship diagram for revenue cycle.